Dendritic cells: Understanding immunogenicity - Steinman, Ralph M (European journal of immunology, 2007)
The impetus for the discovery of dendritic cells in 1972 was to understand immunogenicity, the capacity of an antigenic substance to provoke immunity. During experiments to characterize "accessory" cells that enhanced immunity, we spotted unusual stellate cells in mouse spleen. They had a distinct capacity to form and retract processes or dendrites and were named dendritic cells (DC). DC proved to be different from other cell types and to be peculiarly immunogenic when loaded with antigens. When Langerhans cells were studied, immunogenicity was found to involve two steps: antigen presentation by immature DC and maturation to elicit immunity. Antigen-bearing DC were also immunogenic in vivo and were therefore termed "nature's adjuvants". Several labs then learned to generate large numbers of DC from progenitors, which accelerated DC research. Tolerogenicity via DC, including the control of foxp3⁺ suppressor T cells, was recently discovered. Two areas of current research that I find intriguing are to identify mechanisms for antigen uptake and processing, and for the control of different types of immunity and tolerance. These subjects should be studied in vivo with clinically relevant antigens, so that the activities of DC can be better integrated into the prevention and treatment of disease in patients.